The Relationship between Renewable Energy and Blockchain as a Sustainable Technology Tool - Cristian Bogdan Onete; Sonia Budz; Ioana Bucur-Teodorescu; Sandra Diana Chița; Stefan Sava; Constantin Bucur (Amfiteatru Economic, 2023)
The European Union is accelerating its transition to energy independence by 2030 in response to new geopolitical realities. This study aims to demonstrate the advantages of blockchain technology for the energy sector and how renewable sources themselves may lower costs and generate significant amounts of electricity. These networks encourage the use of renewable energy sources in place of conventional ones and enable sustainable consumption reduction at the same time. The paper demonstrates how blockchain may connect to renewable energy sources, most often solar and wind, to grow this industry in a sustainable way. New technologies like blockchain have sparked the emergence of contemporary forms of trade and consumption. The collaborative and circular economies represent a nexus of economic, technological, and socio-cultural phenomena brought about by technological advancements and economic disruption. Blockchain technology offers a wide range of non-financial applications, and its use is acknowledged as a brand-new opportunity for sustainability and energy. The goal of this study is to clarify the relationship between the two and determine whether blockchain technology can be sustainable for the development of the energy market. The paper is addressed to all parties involved in the energy, blockchain, and sustainability industries.
Keywords: D16; O44; Q20; Q40; Q55; 330; renewable energy; blockchain; sustainability